6q24 Transient Neonatal Diabetes – How to Manage while Waiting for Genetic Results - Fudvoye, Julie; Farhat, Khaldoun; De Halleux, Virginie; Nicolescu, Corina Ramona (Frontiers in Pediatrics, 2016)
Diabetes, rare in the neonatal period, should be evoked in every newborn presenting with unexplained intrauterine and early postnatal growth retardation. This case report illustrates the clinical course and therapeutic approach of a newborn diagnosed with transient diabetes. The baby was born at 37 weeks of gestation with a severe intrauterine growth restriction. Except a mild macroglossia and signs of growth restriction, physical examination was normal. On the 5th day of life hyperglycemia (180 mg/dl) was noted and the next day the diagnosis of diabetes was confirmed (high blood sugar, glucosuria, undetectable levels of insulin and C-peptide). Insulin infusion, initially intravenously and then subcutaneously was started, tailored to assure the growth catch-up and normalize the blood sugar levels. At the age of 4 weeks, the baby returned at home under pump. At 8 weeks, the clinical impression of evolution to a transient diabetes (decreasing needs of insulin with very satisfactory weight gain) was genetically confirmed (paternal uniparental disomy of chromosome 6). There is no screening for neonatal diabetes, but the clinical suspicion avoids the metabolic decompensation and allows early initiation of insulin therapy. The genetic approach (for disease itself and its associated features) relies on timely clinical updates.